Heme Oxygenase1 Level in Normotensive Pregnancy and Preeclampsia with Severe Features - Christian Homenta; John J Wantania; Juneke J Kaeng (Indonesian Socety of Obstetrics and Gynecology, 2016)
Objective: To understand the relationship of heme oxygenase-1 (HO-1) level between normotensive pregnancy and preeclampsia with severe features. Method: The cross sectional study was conducted in the Department of Obstetrics and Gynecology, Faculty of Medicine, Universitas Sam Ratulangi/Prof. Dr. R. D. Kandou General Hospital Manado. The subjects consisted of 26 pregnant women with normal blood pressure and 26 women with severe features of preeclampsia. We took the patients’ history, general physical examination, and laboratory assessment. The blood samples were taken from normotensive women more than 20 weeks of pregnancy and preeclamptic women with severe features more than 20 weeks of pregnancy. The data obtained was processed using SPSS 20.0 software. We did the nonparametric Mann-Whitney test to analyze the relationship between heme oxygenase-1 (HO-1) level in normotensive pregnancy and preeclampsia with severe features. Result: The level of heme oxygenase-1 (HO-1) in normotensive pregnant women was at 3.24 (SD 0.58) ng/ml (95% CI 3.00-3.47), and the level of heme oxygenase-1 (HO-1) of preeclamptic women with severe features was 3.92 (SD 0.73) ng/ml (95% CI 3.62-4.21). The result of Mann-Whitney test showed p value of 0.001 which meant that there was significant difference in the level of heme oxygenase- 1 (HO-1) between normotensive women and pre-eclamptic women with severe features. Conclusion: There was the relationship between the level of heme oxygenase-1 (HO-1) and the incidence of preeclampsia with severe features. Keywords: heme oxygenase-1 (HO-1), normotensive pregnancy, preeclampsia with severe features